Students` Learning Outcomes in Consumer Education in Elementary School - Danilāne, Līga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The global economic crisis and the current conditions of market economy require an intelligent, spiritually rich, open-minded, creative, educated, skilled individual who is able to offer himself/herself in the labour market and promote his/her consumer education and participation in society during the economic downturn. Each person faces the increasing diversity of decision making daily in both personal and public life as responsible citizens in a democratic society, effective participants of global economy, knowledgeable consumers, enterprising and productive workers and competent decision makers. The research is carried out within the framework of the PhD thesis "Essence of Consumer Education in Elementary School" that aims to analyze consumer education content within elementary education, pupils' needs in the field of consumer education and create the appropriate learning content. The paper analyzes pupils' learning outcomes in consumer education in the context of sustainability.